Enthalpy thematic map interpolated with spline method for management of broiler chicken production - Natália C. da Silva; Rodrigo C. Santos; Rafael Zucca; Luciano O. Geisenhoff; Rafaela S. Cesca; Juliano Lovatto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Owing to the exponential growth of the human population and problems related to food supply, research focused on finding the most suitable approach to manage and geographically explore the environment using sustainable technologies stand out. The present study aims to produce a consistent interpolation of historical series of enthalpy (H) resulting in a thematic map of enthalpy, using the spline method as a kriging option in areas with few sampling points. The thematic map considers thermal comfort conditions to produce broiler chickens, that could be used as a management tool to reduce power consumption due to the cooling process of the facilities. It was verified that spline is an efficient method to create a suitable thematic maps representations of areas presenting a few sampled units. The geographical representation of enthalpy allowed the evaluation of the environments, concluding that the state of Mato Grosso do Sul, Brazil is inadequate for broiler chickens production without suitable thermal cooling systems. Evidence suggests introduction of aviculture in areas still unexplored, e.g., Chapadão do Sul and Sete Quedas.